If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4x = 2x + 8 Reorder the terms: 8 + -4x = 8 + 2x Add '-8' to each side of the equation. 8 + -8 + -4x = 8 + -8 + 2x Combine like terms: 8 + -8 = 0 0 + -4x = 8 + -8 + 2x -4x = 8 + -8 + 2x Combine like terms: 8 + -8 = 0 -4x = 0 + 2x -4x = 2x Solving -4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4x + -2x = 2x + -2x Combine like terms: -4x + -2x = -6x -6x = 2x + -2x Combine like terms: 2x + -2x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| (29b-1)-7(4b+1)=-6 | | -4x-8=-2x+12 | | -(6y+4)-(-5y-6)=-1 | | 16(t-6)+5t=7(3t+5)-8 | | 19-22=-3x | | 16-4(x+2)=2x+8 | | 0.4x=0.32 | | (4x+2)(3+5x)= | | 11x=-17+39 | | -16x-4x=-5 | | 6r^2=1 | | -5(x+6)=-10 | | 9y+8-17y+2= | | 8w+7=-3w-15 | | 2y-3x=36 | | 9+5= | | 10x+7.5=80 | | 45-4x=5x+15 | | 5s-3=2s+6 | | 8y-7=6y | | -5x-2y=3 | | 8p-4p-(p-7)+9p+13=12p | | 12+5y=3 | | 3(x+1)+2= | | 4x-13x=63 | | -5x-2y+3=0 | | 2x+8=-37-7x | | 7x+(x-2)=22 | | 8u+5=7u-21 | | 9d-7=11 | | 2+5y=3 | | 2x+4x=24 |